Neuroscience Studies: Contributions to Research in Mesenchymal Stem Cell Culture - Salazar Vargas, Geraldine Zidae (2018)
Tissue repair is one of the great current challenges in regenerative medicine and the mesenchymal stem cells MSCs are the answer to this need because of the multipotential, immunosuppressive, anti-inflammatory and paracrine effects. In the present work, we describe the technique of enzymatic isolation and in vitro culture of MSCs from a real sample of adipose tissue. This will respond to the need for a set of tools necessary in the clinical practice of therapy by stem cells, autotransplant and surgical in different medical specialties and in the field of research as a potential tool for studies of toxicity and in vitro medium lethal dose . It points out the importance that the topic can have for psychology, psychiatry and neurology.